A plated dinosaur (Ornithischia, Stegosauria) from the Early Cretaceous of Argentina, South America: an evaluation - Pereda Suberbiola, Xabier (2013)
A re-evaluation of several vertebrae and dermal plates from the Lower Cretaceous (La Amarga Formation, Puesto Antigual Member; Barremian-lower Aptian) of Neuquén in Argentina, originally described as a stegosaurian dinosaur and recently referred to an indeterminate ornithischian, confirms the former identification. The Neuquén remains have a combination of features that is only known among stegosaurs: cervical vertebrae with a proportionally large cross-section of the neural canal, the anterior height and width of which are half the height of the anterior centrum, as in the cervical vertebrae of Kentrosaurus, Dacentrurus and Stegosaurus; prominent lateral depressions on the cervical centra, as in the presacral vertebrae of Dacentrurus; and cervical dermal plates that are subtriangular, longer than high and reminiscent of those of Miragaia. Moreover, a small bone here interpreted to be an anterior supraorbital (= first palpebral) is similar to that of Stegosaurus and other stegosaurs in having an elongate form and a dorsal rugose surface. The remains from Argentina exhibit some differences relative to other stegosaurs, suggesting that it is potentially a distinct taxon, but their incompleteness advises against the erection of a new genus and species. Interestingly, it is the only known skeletal record of Stegosauria in South America. It provides the second conclusive evidence of the presence of this clade in the Early Cretaceous of the Gondwanan landmasses.